Genetic and morphometric markers are able to differentiate three morphotypes belonging to Section Algarobia of genus Prosopis (Leguminosae, Mimosoideae) - Ferreyra, Laura Ines (2013)
The section Algarobia of genus Prosopis includes promising species for reforestation and afforestation programmes in arid and semiarid regions, mainly of the Americas. Many interspecific natural hybrid combinations have been described in this group. In this paper we analysed a hybrid zone in Chaco biogeographical province in Argentina, where P. ruscifolia and P. alba overlap and hybridise producing intermediate fertile hybrid forms. Eleven morphological traits and 76 loci RAPD were analysed to determine the effect of hybridization between these species. The comparison of morphological traits among groups yielded significant or highly significant differences for all traits. Estimates of H e in P. alba and P. ruscifolia did not differ from each other, but both showed significantly lower values than the hybrid group. The analysis of correlations between shared phenotypes and pair-wise relationships estimated from RAPD gave also strong support to the hypothesis that most of the phenotypic traits analysed have significant heritability. The analyses of population structure and clustering based on morphological and molecular data by DAPC and STRUCTURE were rather consistent and indicated that the three morphotypes studied here are differentiated with low overlapping. All results indicated that despite the occurrence of natural hybridization and introgression, interspecific gene flow would be limited by hybrid breakdown or natural selection favouring the maintenance of species integrity.